Not just energy, but momentum and angular momentum too: Mechanical effects in scattering - T. A. Nieminen (Atti della Accademia Peloritana dei Pericolanti : Classe di Scienze Fisiche, Matematiche e Naturali, 2011)
We review the transport and transfer of momentum and angular momentum by electromagnetic waves, and applications of the mechanical effects of scattering.